Entrepreneurship and paths to business ownership - Cooper, Arnold C.; Dunkelberg, William C. (Strategic Management Journal, 1986)
Abstract Alternative paths to ownership are examined, including starting, purchasing or inheriting a firm, as well as being promoted or brought in by existing owners. It is hypothesized that these involve different ‘degrees of entrepreneurship’, which will be reflected in the profiles of owner‐managers who have followed each path. Data on 1756 owner‐managers are used to test hypotheses relating path to ownership to: the entrepreneurs' background characteristics; motivations and attitudes; and previous careers, incubator organizations and processes of starting.